The Malaysian Chinese homeland consciousness and Fang Beifang's novels - Fan, P.W.; Thock, K.P. (2011)
This article will discuss the transformation of homeland consciousness in Fang Beifang's novels against the background of the gradual localization of Malaysian Chinese literature. Begining with an immigrant identity in the early days, the Chinese gradually realized the importance of localization, and a patriotic consciousness emerged after Malaysia attained its independence. A prominent Malaysian Chinese author Fang Beifang based his works mainly on historical events, enriched with his personal experience and the flavor of the period. Fang Beifang's major works include The Trilogy of Wind and Cloud and The Trilogy of Torrent. The former is set during the anti-Japanese war in China, whereas the latter sums up his real life experiences in Malaya/Malaysia. His works record the Chinese's contribution to the development of Malaysia, as well as the national identity and political dilemmas faced by the Malaysian Chinese community.